2011
DOI: 10.1080/22311866.2011.10719075
|View full text |Cite
|
Sign up to set email alerts
|

Review onArtemisia nilagirica(Clarke) Pamp

Abstract: Natural products are the main stay of the alternative system of medicine. Artemisia nilagirica is commonly known as the Indian wormwood, family Asteraceae, found in the hilly areas of India. The plant has shown noticeably significant pharmacological activities. Traditionally, it is used in management of epilepsy, nervous disorders, as diuretic, anti-inflammatory and skin disorders. In the recent past, various actions of aerial parts are studied and it was found to possess antimicrobial, antifungal, antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
(5 reference statements)
1
12
0
Order By: Relevance
“…A. abrotanum L., A. absinthium L., A. arborescens, A. chamaemelifolia, A. capillaris Thunb., A. indica Willd., A. vulgaris, A. afra, A. annua L., A. caruifolia, A. cina, A. dracunculus L., A. herba-alba, A. japonica Thunb. These species contain the phytochemicals such as, coumarins, terpenoids, flavonoids, caffeoylquinic acids, coumarins, acetylenes and sterols (Martinez-Diaz et al, 2015, Singh et al, 1989, Suresh et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A. abrotanum L., A. absinthium L., A. arborescens, A. chamaemelifolia, A. capillaris Thunb., A. indica Willd., A. vulgaris, A. afra, A. annua L., A. caruifolia, A. cina, A. dracunculus L., A. herba-alba, A. japonica Thunb. These species contain the phytochemicals such as, coumarins, terpenoids, flavonoids, caffeoylquinic acids, coumarins, acetylenes and sterols (Martinez-Diaz et al, 2015, Singh et al, 1989, Suresh et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Leaves are alternate, large, ovate and lobbed, deeply pinnatisect with small stipule-like lobes at the base, pubescent above, ash-grey or white-tomentose beneath; upper most leaves are smaller, 3-fid or entire, lanceolate. The flowers are small and stand in long narrow clusters at the top of the stem, subglobose heads, in spicate or sub erect or horizontal panicled racemes [4]. They are brownish yellow in colour.…”
Section: Plant Descriptionmentioning
confidence: 99%
“…Artemisia nilagirica is an important medicinal plant, which belongs to the family Asteraceae and is popularly known as Indian Wormwood (Suresh et al 2011). The plant is popularly known in India by different vernacular names like Davana (Hindi), Dayona (Odia), Nagadana (Bengali), Leibakngou (Manipuri), Gondhomaro (Marathi), Masipatri (Telugu) etc.…”
Section: Introductionmentioning
confidence: 99%
“…In India, it is widely grown in Himachal Pradesh, Uttarakhand, Rajasthan, Tamil Nadu, Kerala, West Bengal and Sikkim (Joshi et al 2016). It is widely used as anti-inflammatory, skin disorders, antiasthmatic, antimicrobial, antifungal, anticancer, antiulcer, antioxidant, mosquito larvicidal and repellent activities (Suresh et al 2011;Panneerselvam et al 2012;Rani et al 2012;Sati et al 2013;Stappen et al 2014) however, least evidences are found regarding its antimalarial activity (Valecha et al 1994;Shukla et al 2015). Therefore, the present study is designed to evaluate the antimalarial activity of leaf extract of A. nilagirica against P. falciparum.…”
Section: Introductionmentioning
confidence: 99%